'Society gets the education it deserves'. Issue 1 (2nd January 2021) - Jones, Chris
ABSTRACT: Education has the potential to be influenced by society but can also be utilised as a mechanism to enable societal change. Considering the question 'does society get the education it deserves', I utilise Bauman's concept of liquid modernity when exploring the impact of neoliberalist values on the UK education system. These values encourage a consumerist approach to be taken by those entering and within the system and drive competition between providers, which I argue is not conducive to an equality of opportunity for all in society. Without a greater societal response however this paper concludes that the education currently received is one that is deserved.